Inter and intra-reader variability in the threshold estimation of auditory brainstem response (ABR) results. (2nd January 2016) - Zaitoun, Maha; Cumming, Steven; Purcell, Alison; O'brien, Katie
Abstract: Objective : This study aims to examine inter- and intra- reader variability in the ability to estimate hearing threshold through the interpretation of ABR waves of infants. The investigation is based on a large random sample of Australian audiologists. Study design : Sixty-one audiologists were presented with ABR tracings from 15 infants under 12 weeks old. In order to assess inter-rater variability, all cases were presented to all audiologists twice in the same session. Audiologists were asked to nominate a hearing threshold for each of the cases, based purely on their visual judgment of waveforms, and were also asked to answer a brief questionnaire about their experience in ABR testing. Results : Audiologists showed high levels of consistency in reading ABR results. The average inter-reader agreement score was 0.873 and the average intra-reader agreement score was 0.879. Our data show that audiologists' years of experience in ABR testing significantly correlated with their intra-reader agreement scores ( p = 0.004). Conclusion : Audiologists showed a good level of inter- and intra-reader-agreement in ABR interpretation. Years of experience in ABR testing were the main factor that contributed to audiologists' high intra-rater agreement. Therefore, experience in ABR testing is essential in enhancing the outcome of ABR testing and lowering potential misdiagnosis rates.